In situ production of vitamin B12 and dextran in soya flour and rice bran: A tool to improve flavour and texture of B12-fortified bread. (1st May 2022) - Wang, Yaqin; Xie, Chong; Pulkkinen, Marjo; Edelmann, Minnamari; Chamlagain, Bhawani; Coda, Rossana; Sandell, Mari; Piironen, Vieno; Maina, Ndegwa Henry; Katina, Kati
Abstract: This study aimed to develop a fermentation process that allows the concomitant production of dextran (a texture-enhancing agent) and vitamin B12 ( in situ fortification) for bread applications. Mixed fermentation of soya flour or rice bran using Propionibacterium freudenreichii DSM 20271 and Weissella confusa A16 with added sucrose resulted in substantial quantities of dextran (5.6–5.8% dry matter) and B12 (7.9–8.9 μg/100 g fresh weight), together with antifungal metabolites (e.g. acetic and propionic acids). In addition to an extended mould-free shelf life, the bread containing 50% (dough weight) fermented soya flour or rice bran not only contained adequate levels of B12 but also exhibited improved texture and sensory quality compared to the control, such as a higher loaf volume, a softer crumb, and a more cohesive and moister mouthfeel. The mixed fermentation reduced the beany or cooked-rice flavour but increased sour and cheesy flavours and aftertaste. Dextran produced during the fermentation process exhibited a masking effect on the beany and sour notes and aftertaste, consistently with reduced levels of green or grassy volatiles (e.g. hexanal, heptanal, ( E, E )-2, 4-decadienal, and 2-pentylfuran). Overall, the mixed fermentation method using P. freudenreichii DSM 20271 and W. confusa A16 showed potential for B12 fortification of bread products with high sensory quality. Highlights: Fermentation simultaneously produced dextran, vitamin B12, and propionate. This led to improved texture quality and microbial shelf life of fortified bread. Dextran exhibited a flavour-masking effect e.g. on beany and sour notes. This was linked to less beany/green volatile compounds based on SPME-GC-MS. Consuming 100 g of fortified bread would meet the recommended daily intake for B12.